7-ketocholesterol induces endothelial-mesenchymal transition and promotes fibrosis: implications in neovascular age-related macular degeneration and treatment - Wang, Haibo; Ramshekar, Aniket; Kunz, Eric; Hartnett, M. Elizabeth (Angiogenesis (London), 2021)
Oxidized cholesterols and lipids accumulate in Bruch’s membrane in age-related macular degeneration (AMD). It remains unknown what causal relationship exists between these substances and AMD pathophysiology. We addressed the hypothesis that a prevalent form, 7-ketocholesterol (7KC), promotes choroidal endothelial cell (CEC) migration and macular neovascularization in AMD. Compared to control, 7KC injection caused 40% larger lectin-stained lesions, but 70% larger lesions measured by optical coherence tomography one week after laser-injury. At two weeks, 7KC-injected eyes had 86% larger alpha smooth muscle actin (αSMA)-labeled lesions and more collagen-labeling than control. There was no difference in cell death. 7KC-treated RPE/choroids had increased αSMA but decreased VE-cadherin. Compared to control-treated CECs, 7KC unexpectedly reduced endothelial VE-cadherin, CD31 and VEGFR2 and increased αSMA, fibroblast activation protein (FAP) and transforming growth factor beta (TGFβ). Inhibition of TGFβ receptor-mediated signaling by SB431542 abrogated 7KC-induced loss of endothelial and increase in mesenchymal proteins in association with decreased transcription factor, SMAD3. Knockdown of SMAD3 partially inhibited 7KC-mediated loss of endothelial proteins and increase in αSMA and FAP. Compared to control, 7KC-treatment of CECs increased Rac1GTP and migration, and both were inhibited by the Rac1 inhibitor; however, CECs treated with 7KC had reduced tube formation. These findings suggest that 7KC, which increases in AMD and with age, induces mesenchymal transition in CECs making them invasive and migratory, and causing fibrosis in macular neovascularization. Further studies to interfere with this process may reduce fibrosis and improve responsiveness to anti-VEGF treatment in non-responsive macular neovascularization in AMD.